2021
DOI: 10.1111/1346-8138.16201
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of bexarotene for Japanese patients with cutaneous T‐cell lymphoma: Real‐world experience from post‐marketing surveillance

Abstract: To establish real‐world evidence about the safety and efficacy of bexarotene for Japanese patients with cutaneous T‐cell lymphoma, we conducted a nationwide cohort study using data from post‐marketing surveillance for bexarotene treatment. In total, 294 patients with cutaneous T‐cell lymphoma were identified between June 2016 and June 2018. Of these, 267 patients were included as the safety analysis set. Of the 267 patients, 175 were included in the efficacy analysis set. Of these, 139 patients had mycosis fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
2
13
1
Order By: Relevance
“…Our data indicated no difference in the incidence of overall hypertriglyceridemia between the two groups stratified by BMI category. This tendency was consistent with the findings from post‐marketing surveillance 10 . Interestingly, however, our data in this study shows that the occurrence of grade ≥3 hypertriglyceridemia was increased in overweight and obese patients as compared with normal and underweight patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data indicated no difference in the incidence of overall hypertriglyceridemia between the two groups stratified by BMI category. This tendency was consistent with the findings from post‐marketing surveillance 10 . Interestingly, however, our data in this study shows that the occurrence of grade ≥3 hypertriglyceridemia was increased in overweight and obese patients as compared with normal and underweight patients.…”
Section: Discussionsupporting
confidence: 92%
“…However, due to adverse effects of bexarotene treatment, patients on bexarotene require careful monitoring for lipid, thyroid, liver, blood count, creatine kinase, glucose, and amylase abnormalities 6–9 . Among the adverse effects of bexarotene, hypertriglyceridemia is clinically problematic 6–10 . Despite lifestyle management and prophylactic use of lipid‐lowering agents, hypertriglyceridemia is often unavoidable in patients on bexarotene 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although flow cytometers are widely used for diagnosing CTCL subtypes, they are difficult to use if the number of infiltrating cells is limited, such as the early stage of MF and drug eruptions. Digital microscopic analysis is useful for quantitative analysis of immunohistochemical staining, especially to identify the profiles of lymphocytes such as TILs [9, 10]. For example, we previously evaluated TILs in metastatic melanoma, the profile of which is dramatically changed by the administration of nivolumab plus ipilimumab combined therapy [10].…”
Section: Discussionmentioning
confidence: 99%
“…Digital microscopic analysis is useful for quantitative analysis of immunohistochemical staining, especially to identify the profiles of lymphocytes such as TILs [9, 10]. For example, we previously evaluated TILs in metastatic melanoma, the profile of which is dramatically changed by the administration of nivolumab plus ipilimumab combined therapy [10]. These reports suggested that digital microscopic analysis is even useful for the analysis of profiles of CTCL instead of flow cytometry.…”
Section: Discussionmentioning
confidence: 99%